Panoramic stitching with variable zoom - Adi Putra Wijaya (2010)
Many digital cameras offers a "panorama" mode, in which the camera stitches together overlapping shots to provide a 180 degree field of view. During the panorama acquisition, the user cannot adjust the zoom or focus of the lens. This limitation prevents the user from, for example, creating panoramas containing regions of interest with higher resolution.